Power of positive words: communication, cognition, and organizational transformation. Issue 1 (11th February 2019) - Muthusamy, Senthil Kumar
Abstract : Purpose: In the extant organizational change literature scant attention has been given to the communication and cognitive processes consequential to organizational transformation. From the communication and sense-making perspectives, this study discusses the role of positive communication involving stories, metaphors or axioms in fostering socio-cognitive routines necessary for organizational change. The study further examines the empirical link between positive communication and organizational transformation with the survey data from professionals who have experienced the organizational change episode. The paper aims to discuss these issues. Design/methodology/approach: The study examines the empirical link between the positive communication and organizational transformation with a survey data collected from 174 management professionals who have recently experienced the organizational change episodes such as restructuring, reengineering, TQM adoption or new strategy implementation. With the content analysis of narratives containing metaphors, axioms and stories, the study unravels the underlying clusters of organizational and socio-cognitive dimensions associated with organizational transformation. Findings: The study results affirm the importance of positive communication and its effects on the emotional buy-in, learning and transformation occurring at the individual level, and attest to the transformational effect of positive axioms, metaphors or stories on the organization. The study also revealed that the positive communication diffusing social, cognitive or emotional attributes such as commitment, trust or optimism produces the desired transformational effect. Practical implications: It is imperative for managers to understand the relationship between socio-linguistic processes and cognitive attributes such as trust, commitment and learning. With the help of right metaphors, stories and axioms that resonate with changing industry conditions, managers can effectively orchestrate the strategic intent and organizational transformation. Originality/value: Most studies on the relationship between managerial communication and organizational transformation are primarily qualitative case studies focusing on the dialectics of organizational change. This study carries the strong external validity by capturing the connection between managerial communications and their transformational effect with the help of data collected from the management professionals across multiple industries.